The antecedents and consequences of workrelated musculoskeletal disorders (WRMDs) among administrative workers in Peninsular Malaysia / Mohd Zulkifli Abdullah - Abdullah, Mohd Zulkifli (Institute of Graduate Studies, UiTM, 2015)
Productivity is an important indicator of economic growth and social health. It is vital in identifying key factors that are described to workers’ health in their workplace and life. Work-related musculoskeletal disorders (WRMDs) are becoming prevalence among the administrative workers around the world due to increase workrelated stress instigated by structured and routine workloads which put extreme pressures on their physical and emotional states. This occurrence instigates stress to upsurge, making workers vulnerable to WRMDs. In a highly demanding working environment, the problem of WRMDs is getting more serious as compared to previous days. This phenomenon brings significant negative effect on the productivity of the employees. More recently, psychosocial factors in the work environment have been considered; however, findings across these studies have not been consistent. Therefore, the present study was conducted to investigate the factors that contribute to the prevalence of WRMDs such as psychosocial factors and stress, and to examine the influence of WRMDs on employees’ productivity i.e. absenteeism as well as presenteeism…